Conversion attribution: What is missed by the advertising industry? The OPEC model and its consequences for media mix modeling - Arkadiusz Zaremba (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
Marketers are currently focused on proper budget allocation to maximize ROI from online advertising. They use conversion attribution models assessing the impact of specific media channels (display, search engine ads, social media, etc.). Marketers use the data gathered from paid, owned, and earned media and do not take into consideration customer activities in category media, which are covered by the OPEC (owned, paid, earned, category) media model that the author of this paper proposes. The aim of this article is to provide a comprehensive review of the scientific literature related to the topic of conversion attribution for the period of 2010-2019 and to present the theoretical implications of not including the data from category media in marketers' analyses of conversion attribution. The results of the review and the analysis provide information about the development of the subject, the popularity of particular conversion attribution models, the ideas of how to overcome obstacles that result from data being absent from analyses. Also, a direction for further research on online customer behavior is presented.
Keywords: M31; M37; 650; online customer journey; budget allocation; multi-channel conversion attribution; paid owned earned category media